The role of EZH2 in overall survival of colorectal cancer: a meta-analysis - Vilorio-Marqués, Laura; Martín, Vicente; Diez-Tascón, Cristina; González-Sevilla, María Francisca; Fernández-Villa, Tania; Honrado, Emiliano; Davila-Batista, Veronica; Molina, Antonio J. (Scientific reports, 2017)
Enhancer of zeste homolog 2 (EZH2) is the catalitic subunit of polycomb repressive complex 2 and mediates gene silencing. EZH2 is overexpressed in many cancers and correlates with poor prognosis. The role of the gene EZH2 in colorectal cancer survival is uncertainly, the aim of this study is clear this relationship. Relevant literaure was searched from electronic databases. A meta-analysis was performed with elegible studies which quantitatively evaluated the relationship between EZH2 overexpression and survival of patients with colorectal cancer. Survival data were aggregated and quantitatively analyzed. We performed a meta-analysis of 8 studies (n = 1059 patients) that evaluated the correlation between EZH2 overexpression and survival in patients with colorectal cancer. Combined hazard ratios suggested that EZH2 overexpression was associated with better prognosis of overall survival (OS) HR(hazard ratio) = 0.61 95% CI (0.38–0.84) We performed bias analysis according Egger and Begg,s test and we did not find publication bias. EZH2 overexpression indicates a better prognosis for colorectal cancer.